OpenMP in a Heterogeneous World 8th International Workshop on OpenMP, IWOMP 2012, Rome, Italy, June 11-13, 2012. Proceedings - Chapman, Barbara; Massaioli, Federico; Müller, Matthias S.; Rorro, Marco (Programming and Software Engineering, 2012)
This book constitutes the refereed proceedings of the 8th International Workshop on OpenMP, held in in Rome, Italy, in June 2012. The 18 technical full papers presented together with 7 posters were carefully reviewed and selected from 30 submissions. The papers are organized in topical sections on proposed extensions to OpenMP, runtime environments, optimization and accelerators, task parallelism, validations and benchmarks.